Preparation of artificial graphite coated with sodium alginate as a negative electrode material for lithium-ion battery study and its lithium storage properties. Issue 24 (2nd November 2022) - Rao, Xianfa; Zhang, Lixia; Li, Baobao; Zeng, Xinxiong; Xiao, Wenlong; Lou, Yitao; Xie, Huanmeng; Yan, Huchen; Yi, Zixuan; Zhong, Shengwen
Abstract : Artificial graphite has problems such as electrolyte erosion during long cycle and unstable lamellar structure. Sodium alginate (SA) coating modified graphite anode was proposed and obtained to effectively solve the above problems. Abstract : In this paper, artificial graphite is used as a raw material for the first time because of problems such as low coulomb efficiency, erosion by electrolysis solution in the long cycle process, lamellar structure instability, powder and collapse caused by long-term embedment and release of lithium ions when it is used as a cathode material. The strategy of modifying a graphite anode with a sodium alginate (SA) coating was proposed and a 5.0% SA-1000 composite anode material was obtained. As a result of using sodium alginate (SA) to coat graphite particles, the SEI film formed was stable and compatible with electrolytes. One benefit of the coating is that it limits the amount of irreversible lithium consumed during film formation. Compared with artificial graphite, the first specific capacities of the initial charge and discharge (412.809 mA h g −1 and 472.067 mA h g −1 ) of the 5.0% SA-1000 composite anode material are significantly increased. Furthermore, the organic coating reduces the interface impedance between the electrolyte and the negative electrode. After 600 cycles, the reversible capacity of the composite remains at 48.298 mA h g −1, significantly improving the cyclic stability of graphite. On the other hand, the introduction of sodium alginate improved the migration of lithium ions inside and outside of the graphite, and the reversible capacity of the 5.0% SA-1000 composite sample is 461.197 mA h g −1, 444.457 mA h g −1, 386.633 mA h g −1, 304.794 mA h g −1, 140.846 mA h g −1 and 72.196 mA h g −1 at 100 mA g −1, 200 mA g −1, 300 mA g −1, 500 mA g −1, 1000 mA g −1 and 2000 mA g −1, respectively. When compared with graphite samples at the same magnification, 5.0% SA-1000 significantly improved its reversible capacity and stability, especially at 300 mA g −1 and 500 mA g −1 . Its reversible capacities were increased by 196.911 mA h g −1 and 184.818 mA h g −1 . Therefore, 5.0% SA-1000 composites make it possible to improve the lithium storage capacity of lithium-ion batteries.